Implementasi Digital Marketing Pembuatan Website Penjualan Dengan Metode Agile: (Studi Kasus: Danisty Olshop) - Winarti; Rina Noviana; Devi Indriani; Dewi Andryani; Kartika Nor Ramadha; Isram Rasal; Rifki Amalia; Aryo Pangestu (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2026)
Danisty Olshop is a shop that sells vehicle cleaning products through various e-commerce platforms and social media. This research is motivated by the need to increase operational efficiency and increase the competitiveness of digital marketing which is able to reach wider customers through the creation of sales websites. The aim of this research is to create a responsive e-commerce platform that supports effective digital marketing strategies in the form of a website, using Agile methods that allow continuous adjustment according to user needs. The website uses PHP programming and a MySQL database. The website is designed for two users, namely the user as a customer who purchases products and the admin as a seller who has access to manage products and monitor transactions. The results of the implementation and trial of the website that have been created meet expectations and are ready to be accessed via the link https://danistyolshop.my.id/. The application of the Agile method during the manufacturing process provides high flexibility and responsiveness according to user needs, so that implementing an integrated digital marketing strategy can expand market reach and increase sales significantly